Influence of Grain Boundary Structural Evolution on Pressure Solution Creep Rates. Issue 10 (24th October 2019) - van den Ende, M. P. A.; Niemeijer, A. R.; Spiers, C. J.
Abstract: Intergranular pressure solution is a well‐known rock deformation mechanism in wet regions of the upper crust and has been widely studied, especially in the framework of compaction of granular materials, such as reservoir sandstones and fault rocks. Several analytical models exist that describe compaction creep by stress‐induced mass transport, and the parameters involved are relatively well constrained by laboratory experiments. While these models are capable of predicting compaction behavior observed at relatively high porosities, they often overestimate compaction rates at porosities below 20% by up to several orders of magnitude. This suggests that the microphysical processes operating at low porosities are different and are not captured well by existing models. The implication is that available models cannot be extrapolated to describe compaction of sediments and fault rocks to the low porosities often reached under natural conditions. To address this problem, we propose a new, thermodynamic model that describes the decline of pressure solution rates within individual grain contacts as a result of time‐averaged growth of asperities or islands and associated constriction of the grain boundary diffusion path (here termed grain boundary evolution). The resulting constitutive equations for single grain‐grain contacts are then combined and solved semianalytically. The compaction rates predicted by the model are compared with those measured in high‐strain compaction experiments on wet granular halite. A significant reduction in compaction rate is predicted when grain boundary evolution is considered, which compares favorably with the experimental compaction data. Key Points: A new model is presented for the structural evolution of stressed grain boundaries undergoing pressure solution This model is tested against laboratory single‐contact and granular aggregate compression tests The model reconciles classical pressure solution theory with laboratory observations of aggregate compaction at low porosities